Evaluation of vehicle braking parameters by multiple regression method - DEMİR, ABDULLAH (SHARIF UNIV TECHNOLOGY, 2019)
This study uses two pairs of OEM brake disc-pads. One of these discs belongs to a passenger car and the other one to a light commercial vehicle. The disc-pad pair of the passenger car is subject to the global brake effectiveness test by a full-scale inertia dynamometer according to SAE J2522 test standard; the other one is subject to the tests by a full-scale inertia dynamometer according to Fiat 7-H4020 and 7-112000 standards. During these tests, 13 variables for the passenger car disc-pad pair and 11 variables for light commercial vehicle disc-pad pair were measured and recorded. The interrelation of the parameters was analyzed by the multiple regression method, and importance levels were determined. In this study, dependent variables in the multiple regression method including braking time, friction coefficient, disc final temperature, brake speed, and brake pressure were selected for each braking pair. In multiple regression analysis concerning the passenger car, for each unit of increase in deceleration and friction coefficient, braking time decreases with 7.3 and 60.9 units, respectively. Moreover, for each unit of increase in brake pressure and friction coefficient for the light commercial vehicle, braking time increases with 1.267 and 91.887 units, respectively. (C) 2019 Sharif University of Technology. All rights reserved.
Keywords: Braking parameters; Braking performance; Friction coefficient; Brake disc-pad pair; Multiple regression method; PAD; PERFORMANCE